On the identity of Cancer saxatilis Herbst, 1785: an objective synonym of Lophozozymus pictor (Fabricius, 1798), by neotype designation and reversal of precedence (Crustacea: Decapoda: Brachyura: Xanthidae: Zosiminae) - Low, Martyn E. Y. (Zootaxa, 2012)
The name Cancer saxatilis was used by Herbst (1785: 187, 188) for the translated description and cited figure of “Cancer saxatilis” from the pre-Linnaean work of Rumphius (1705: 9, 10, pl. 5, fig. M). Cancer saxatilis Herbst, 1875, is an available name as it fulfils the requirements of Articles 3–12 of the International Code of Zoological Nomenclature (hereafter the Code, ICZN 1999). The description and figure of “Cancer saxatilis” Rumphius (1705), and therefore Cancer saxatilis Herbst, 1785, are readily identifiable with Lophozozymus pictor (Fabricius, 1798) (see Ng & Chia 1995: 428).